Haptoglobin is dispensable for haemoglobin uptake by Trypanosoma brucei - Horáková, Eva; Vrbacký, Marek; Tesařová, Martina; Stříbrná, Eva; Pilný, Jan; Vavrušková, Zuzana; Vancová, Marie; Sobotka, Roman; Lukeš, Julius; Perner, Jan (Frontiers in Immunology, 2024)
Haptoglobin is a plasma protein of mammals that plays a crucial role in vascular homeostasis by binding free haemoglobin released from ruptured red blood cells. Trypanosoma brucei can exploit this by internalising haptoglobin-haemoglobin complex to acquire host haem. Here, we investigated the impact of haptoglobin deficiency (Hp-/-) on T. brucei brucei infection and the parasite´s capacity to internalise haemoglobin in a Hp-/-mouse model. The infected Hp-/-mice exhibited normal disease progression, with minimal weight loss and no apparent organ pathology, similarly to control mice. While the proteomic profile of mouse sera significantly changed in response to T. b. brucei, no differences in the infection response markers of blood plasma between Hp-/-and control Black mice were observed. Similarly, very few quantitative differences were observed between the proteomes of parasites harvested from Hp-/-and Black mice, including both endogenous proteins and internalised host proteins. While haptoglobin was indeed absent from parasites isolated from Hp-/-mice, haemoglobin peptides were unexpectedly detected in parasites from both Hp-/-and Black mice. Combined, the data support the dispensability of haptoglobin for haemoglobin internalisation by T. b. brucei during infection in mice. Since the trypanosomes knock-outs for their haptoglobin-haemoglobin receptor (HpHbR) internalised significantly less haemoglobin from Hp-/-mice compared to those isolated from Black mice, it suggests that T. b. brucei employs also an HpHbR-independent haptoglobin-mediated mode for haemoglobin internalisation. Our study reveals a so-far hidden flexibility of haemoglobin acquisition by T. b. brucei and offers novel insights into alternative haemoglobin uptake pathways.